A UTILIZAÇÃO DA FERRAMENTA BIM 5D PARA OBRAS PÚBLICAS NO BRASIL - Viana, Leandro; Arantes, Eduardo (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This article was developed with the purpose of analyzing the applicability of the use of BIM 5D tool for the elaboration of budgets of public works in Brazil. In order to do so, the government's initiatives in this regard were presented, as well as the functionalities of this tool that imply the facilities and gains for the public service in the elaboration of the budget of its works.